Peran Iklan #RambutCapek di Instagram dan X dalam Mendorong Minat Beli Konsumen - Agnes Monica Marpaung; Asep Suryana; Gema Nusantara Bakry (Jurnal Ilmu Komunikasi dan Bisnis, 2025)
The diversity of shampoo brands demands innovative marketing strategies  to highlight their products. The use of male models as the primary representation  in Pantene Indonesia shampoo advertisements is a new step that shifts the  advertising paradigm, which previously always emphasized the feminist side. This  study aims to measure the role of the Pantene Shampoo advertisement "Hair  Supplement Baru! - Bye #RambutCapek Hello #RambutKeCharged" in influencing  consumer purchasing tendencies. The research method employed is a survey  conducted by distributing questionnaires through Google Form to randomly  selected respondents with a sample size of 400 respondents distributed throught  Instagram and X. Data analysis may involve statistical techniques to identify the  role of advertisements in driving purchasing interest, as well as other factors that  may influence consumer interest in a shampoo product. Data processing utilizes  descriptive quantitative methods. The research findings indicate that: (1) Attitude  towards advertisements plays a role in influencing consumer purchasing interest,  (2) Subjective norms play a role in influencing consumer purchasing interest in  advertisements, (3) Behavioral control plays a role in influencing consumer  purchasing interest in advertisements. These research findings can provide insights  for marketers to understand the effectiveness of their advertisements in influencing  consumer behavior, particularly among social media users. Consequently, they can  tailor their marketing strategies to achieve desired objectives.